2020
DOI: 10.1186/s13601-020-00332-z
|View full text |Cite
|
Sign up to set email alerts
|

Distinct type 2-high inflammation associated molecular signatures of chronic rhinosinusitis with nasal polyps with comorbid asthma

Abstract: Background: Patients with chronic rhinosinusitis with nasal polyps (CRSwNP) and comorbid asthma have more severe disease and are difficult to treat. However, the molecular endotypes associated with CRSwNP with comorbid asthma (CRSwNP + AS) are not clear. This study aimed to investigate the characteristics of type 2 inflammation and the molecular signatures associated with CRSwNP + AS. Methods: A total of 195 subjects; including 65 CRSwNP + AS patients, 99 CRSwNP-alone patients, and 31 healthy control subjects;… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 61 publications
(73 reference statements)
4
52
1
Order By: Relevance
“… 20 , 26 IKBKB has been shown to be upregulated in patients with asthma, 16 , 20 and prior CRS data has shown a similar overrepresentation of type 2 inflammation in CRSwNP-A compared to CRSwNP. 4 , 18 , 19 , 25 At the same time, in the present cohort, upregulation of these genes associated with type 2 inflammation was complemented by a simultaneous downregulation of genes associated with type 1 and type 3 inflammation. For example, compared to CRSwNP, patients with CRSwNP-A demonstrated downregulation of genes associated with Th17 differentiation ( MAPK11 ) 27 and Th1 signaling ( PSMB8 and B2M ).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“… 20 , 26 IKBKB has been shown to be upregulated in patients with asthma, 16 , 20 and prior CRS data has shown a similar overrepresentation of type 2 inflammation in CRSwNP-A compared to CRSwNP. 4 , 18 , 19 , 25 At the same time, in the present cohort, upregulation of these genes associated with type 2 inflammation was complemented by a simultaneous downregulation of genes associated with type 1 and type 3 inflammation. For example, compared to CRSwNP, patients with CRSwNP-A demonstrated downregulation of genes associated with Th17 differentiation ( MAPK11 ) 27 and Th1 signaling ( PSMB8 and B2M ).…”
Section: Discussionsupporting
confidence: 66%
“…In contrast, cytokine profiles typically associated with CRSsNP can present as a mixture of type 1 (Th1 cell-mediated), Th2, and type 3 (Th17 cell-mediated) inflammation. 4 , 7 These inflammatory endotypes themselves are influenced by molecular endotypes and associated upstream transcriptional changes that occur in these disease cohorts. 4 Despite this, there is currently very limited data on molecular endotypes among patients with CRS with asthma (CRS-A), with no studies examining this topic in patients with CRSsNP and asthma (CRSsNP-A).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang and colleagues observed that subjects with combined CRSwNP and asthma endotype have more severe T2 inflammatory patterns compared to CRSwNP-alone endotype based on findings from whole-transcriptome RNA sequencing. 35 Based on this evidence, systemic biologic therapy in patients with both upper and lower airway disease may be a reasonable consideration as it can improve both conditions due to shared pathogenic pathways.…”
mentioning
confidence: 99%